Pemberdayaan Masyarakat Dalam Pencegahan Penyakit Demam Berdarah Dengue - Regita Cahyani; Nisrina Nisrina; Maisyah Ardila; Rizka Tiara; Rizka Aulia; Sri Rezky Gantina; Syahril Budiman Pasaribu; Wulan Andika (Jurnal Pengabdian Bidang Kesehatan, 2023)
In Indonesia, dengue fever (DHF) is a health problem that tends to spread more widely and claim more lives due to increasing population density and mobility. The aim of this research is to find out what empowerment can be done to the community to increase public knowledge regarding the prevention of dengue fever (DHF). The research method for this journal is to use a literature study methodology or review journals totaling around 20 journals consisting of 18 national journals and 2 international journals using online sources (Google Scholar). The result of this research is to increase the quality of public knowledge in preventing dengue fever (DHF).